Socialization of Eco Enzyme Utilization for Environmental Health to Gapoktan Seputih Raman, Lampung - Suharti, Bangun; Maryanah, Tabah; Prasetyo, Prayoga Ardhi; Ulhaq, Abdullah Wildan (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Eco enzyme has tremendous benefits for family health, the environment, agriculture and livestock. However, in general, farmers and breeders have not maximally utilized eco enzyme made from fruit peels and eggshells. This PKM activity was carried out to provide experience in making ecoenzyme and understanding and utilizing its many functions to the Seputih Raman farmer group, Central Lampung. This PKM activity was carried out with a demonstration method for making eco enzyme, socializing the benefits of eco enzyme and sharing session monitoring the results of activities in the WA group. From this PKM activity, it was found that the farmer group family (gapoktan) had understood how to make eco enzyme and how to optimize its benefits for various purposes. This PKM activity has been able to enlighten participants, that the use of eco enzyme which is environmentally friendly, can reduce the use of chemical fertilizers which in addition to being expensive, in the long run can damage the environment. Further sharing sessions were carried out using the WA group channel. Through sharing sessions on the benefits of eco enzyme with herbs to overcome various family complaints and diseases, the participants were enthusiastic and increasingly enlightened, in an effort to turn waste into blessings (useful).